2021
DOI: 10.1111/coa.13693
|View full text |Cite
|
Sign up to set email alerts
|

Is elective contralateral neck dissection necessary in 53 salvage total laryngectomy patients?

Abstract: Historically, if the risk of occult nodal disease is >20%, elective neck dissection was advised for surgical management of squamous cell carcinoma (SCC). 1,2 A recent meta-analysis in the salvage laryngectomy setting (n = 1141) reported an occult nodal positivity rate (cN0pN+) of 11%, 3 which was higher in advanced local supraglottic (24%) or transglottic (17%) disease. Therefore, in high-risk patients undergoing salvage laryngectomy, neck dissection is generally recommended.The cN0pN+ disease rate in the cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Hogg et al . 22 reported a 2 per cent risk of contralateral neck disease during salvage total laryngectomy, and therefore recommended avoiding contralateral elective neck dissection during salvage total laryngectomy. In our series, no patient had involvement of levels I or V, and only one patient with a lateralised tumour had contralateral neck disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hogg et al . 22 reported a 2 per cent risk of contralateral neck disease during salvage total laryngectomy, and therefore recommended avoiding contralateral elective neck dissection during salvage total laryngectomy. In our series, no patient had involvement of levels I or V, and only one patient with a lateralised tumour had contralateral neck disease.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the only large series reporting the risk of occult neck disease in a specific neck level according to primary tumour location (but not recurrent stage) 20 showed that the risk of occult neck disease at levels I, IV and V for supraglottic SCC and all levels for glottis SCC (except level VI) was less than 10 per cent, whereas the risk of occult neck disease at levels II, III and VI for supraglottic SCC is more than 10 per cent even on the contralateral side. Hogg et al 22 reported a 2 per cent risk of contralateral neck disease during salvage total laryngectomy, and therefore recommended avoiding contralateral elective neck dissection during salvage total laryngectomy. In our series, no patient had involvement of levels I or V, and only one patient with a lateralised tumour had contralateral neck disease.…”
Section: Lymph Node Distribution Neck Dissection and Survivalmentioning
confidence: 99%